The Mangking Sandstone formation of Kuala Tahan to Kampung Bantal: sedimentology and depositional environment - Khor, Wei Chung; Kamal Roslan Mohamed; Che Aziz Ali; Muhammad Ashahadi Dzulkafli; Jasmi Ab Talib (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Mangking Sandstone of Tembeling Group in the Kuala Tahan region records part of the infill of the continental extensional basin formed at the end of the Triassic. Described facies of this formation include sandy matrix conglomerate (that shows evidence of pseudoplastic debris flow and traction-dominated deposition), sandstones with trough, tabular and horizontal stratification, laminated and massive mudstone. Groups of associated facies are arranged into six distinct architectural elements (channel, sandy bedform, crevasse splay, laminated sand sheet, downstream and lateral accretion and floodplain fines), which are constant with a fluvial origin for the succession. The types of architectural elements present and their relationship to each other demonstrate that the Mangking Sandstone preserves a record of a meandering river system.